Efficacy of N-phenylphtalamic acid in some Solanaceae species - Chauhan, S. V. S.; Singh, H. H.; Gupta, H. K. (International Journal of Horticultural Science, 2005)
: N-phenylphthalamic acid — Cl4H1 1 NO3 (Nevirol 60 WP) was successfully used for enhancing yield in some important vegetable crops namely, tomato (Lycopersicon esculentum), chilli (Capsicum annuum) and brinjal (Solanum melongena) of Solanaceae. Aqueous sprays with 0.2% and 3.0% significantly enhanced fruit production in chilli and tomato respectively. On the other hand, various treatments in brinjal failed to enhance yield significantly. The increase in yield in both tomato and chilli is largely due to increase in the number of flowers and fruit-set percentage.